Clinical Best Practice Advice for Hepatology and Liver Transplant Providers During the COVID‐19 Pandemic: AASLD Expert Panel Consensus Statement - Fix, Oren K. (Hepatology, 2020)
BACKGROUND AND AIMS: Coronavirus disease 2019 (COVID‐19), the illness caused by the SARS‐CoV‐2 virus, is rapidly spreading throughout the world. Hospitals and healthcare providers are preparing for the anticipated surge in critically ill patients, but few are wholly equipped to manage this new disease. The goals of this document are to provide data on what is currently known about COVID‐19, and how it may impact hepatologists and liver transplant providers and their patients. Our aim is to provide a template for the development of clinical recommendations and policies to mitigate the impact of the COVID‐19 pandemic on liver patients and healthcare providers. APPROACH AND RESULTS: This article discusses what is known about COVID‐19 with a focus on its impact on hepatologists, liver transplant providers, patients with liver disease, and liver transplant recipients. We provide clinicians with guidance for how to minimize the impact of the COVID‐19 pandemic on their patients’ care. CONCLUSIONS: The situation is evolving rapidly, and these recommendations will need to evolve as well. As we learn more about how the COVID‐19 pandemic impacts the care of patients with liver disease, we will update the online document available at https://www.aasld.org/about-aasld/covid-19-and-liver.